Adat Bak Poteu Meureuhom and Hukom Bak Syiah Kuala: Symbolic power and Islamic governance in Aceh history - Joko Hariadi; Katimin Katimin; Hasrat Effendi Samosir; Nur Amelia; Tanita Liasna; Indah Fajarini (Universitas Muhammadiyah Malang, 2025)
The philosophies of Adat Bak Poteu Meureuhom, Hukom Bak Syiah Kuala reflect a unique symbiosis between Islamic political communication and local cultural practices in Aceh’s history. These philosophies articulate a balance between customary authority held by the sultan and the religious legal authority exercised by the eminent scholar Syiah Kuala, while simultaneously shaping collective identity and social control within Acehnese society. This study employs a qualitative hermeneutic-historical approach with discourse analysis of historical literature, archives, and local texts to examine symbolic interactions, political narratives, and cultural practices that reinforce legitimacy of power. Findings indicate that, in contemporary contexts, these philosophies are applied in local officials’ speeches, educational curricula, and community rituals, although their meanings have adapted in response to globalization and the special autonomy of Aceh. The symbiosis between adat and sharia emerges as a form of Hybrid Governance, functioning as social capital to build culturally and religiously grounded political legitimacy. This research underscores the relevance of these philosophies as instruments of symbolic communication for preserving local values while navigating modern challenges, contributing to global studies on symbolic power, cultural legitimacy, and Islamic political governance in postcolonial regions. Falsafah Adat Bak Poteu Meureuhom, Hukom Bak Syiah Kuala mencerminkan simbiosis unik antara komunikasi politik Islam dan praktik budaya lokal dalam sejarah Aceh. Falsafah ini menegaskan keseimbangan antara kekuasaan adat yang dipegang oleh raja dan otoritas hukum agama yang dijalankan oleh ulama besar Syiah Kuala, sekaligus membentuk identitas kolektif dan kontrol sosial masyarakat Aceh. Studi ini menggunakan pendekatan kualitatif hermeneutik-historis dengan analisis wacana terhadap literatur sejarah, arsip, dan teks lokal untuk menelaah interaksi simbolik, narasi politik, dan praktik budaya yang memperkuat legitimasi kekuasaan. Temuan menunjukkan bahwa, secara kontemporer, falsafah ini diterapkan dalam pidato pejabat lokal, kurikulum pendidikan, dan ritual komunitas, meskipun maknanya telah mengalami adaptasi terhadap dinamika globalisasi dan otonomi khusus. Simbiosis antara adat dan syariat muncul sebagai bentuk Hybrid Governance, yang berfungsi sebagai modal sosial untuk membangun legitimasi politik berbasis budaya dan agama. Penelitian ini menegaskan relevansi falsafah sebagai instrumen komunikasi simbolik dalam menjaga nilai-nilai lokal sekaligus menghadapi tantangan modernitas, serta memberikan kontribusi pada studi global tentang kekuasaan simbolik, legitimasi budaya, dan politik Islam di kawasan postkolonial.